PERILAKU PEMILIK ATAS ISU MANAJEMEN LINGKUNGAN DILIHAT DARI SEKTOR,REGIONAL DAN UKURAN PERUSAHAAN - Citra Agustina (Business Accounting Review, 2016)
This study aimed to know the differences in the behavior of the owner’s attitude related to environmental management isue in the manufacturing and non-manufacturing companies located in Surabaya and non Surabaya.                        This study was a quantitative research, and the data obtained through questionnaires to the small and large manufacturing and non-manufacturing companies in Surabaya and non Surabaya. The data obtained processed using SPSS software. The results of this study showed a differences in the owner’s attitude concerning with the issues of environmental management on manufacturing and non-manufacturing companies with small and large capacity in Surabaya and Non Surabaya.